ECTIMA: A CASE REPORT - I Gde Julia Arta (E-Jurnal Medika Udayana, 2014)
Ektima a superficial ulcer with crusting on it caused by streptococcus B infection hemolyticus.Ektima incidents worldwide are not known precisely. The frequency of occurrence based on ageektima usually found in children and the elderly, there is no distinction of race and gender (maleand female alike). In most children at age 6 months to 18 years. Diagnosis of the disease ektimamade based on clinical symptoms found in patients and supported by laboratory tests such asGram's staining. Treatment ektima form of topical and systemic treatment. This report discussesthe case Ektima on a boy aged 7 years. These patients receive topical treatment with 0.9% NaClcompress on the wound that is still wet and Mupirocin 2% cream applied thinly 3-4x/day  thelesion and systemic antibiotics such as cefadroxil syrup 2 times daily 1 ½ teaspoons.